Junge Frauen mit Lernschwierigkeiten zwischen Selbst- und Fremdbestimmung Ergebnisse aus einem partizipativen Forschungsprozess - Sigot, Marion (Schriftenreihe der ÖFEB-Sektion Sozialpädagogik, 2017)
In a participatory research project with women with learning difficulties, the author has researched questions relating to self-determination and self-determination and presents the results here. Through the active involvement of women with learning difficulties, their view of the contents, methods and results of the research is reflected in the jointly planned project.